P‐type Sb‐doped Cu2O Hole Injection Layer Integrated on Transparent ITO Electrode for Acidic PEDOT:PSS‐Free Quantum Dot Light Emitting Diodes. Issue 11 (4th April 2019) - Seo, Hyeong‐Jin; Lee, Ji‐Eun; Heo, Su Been; Kim, Minju; Yi, Yeonjin; Kang, Seong Jun; Kim, Han‐Ki
Abstract : It is developed that transparent p‐type Sb‐doped cuprous oxide (ACO) integrated Sn‐doped In2 O3 (ITO) film as hole injection layer (HIL) and anode combined electrodes for quantum dot light emitting diodes (QD‐LEDs) to substitute acidic PEDOT:PSS HIL based electrode. By graded co‐sputtering of ACO and ITO targets, the graded p‐type ACO buffer layer can be integrated on the surface region of the ITO electrodes. P‐type conductivity of the ACO film for acting as effective HIL in QD‐LEDs is confirmed by a positive Hall coefficient (1.74 × 10 −3 ohm cm 3 /C) and a positive Seebeck constant (115 µV K −1 ). Due to the well‐matched work function of p‐type ACO on the ITO electrodes, the acidic PEDOT:PSS‐free QD‐LEDs exhibited typical current‐voltage‐luminescence of QD‐LEDs. The successful operation of PEDOT:PSS‐free QD‐LED with p‐type ACO integrated ITO electrode indicates that ACO and ITO anode graded sputtering is simpler fabrication steps for cost‐effective QD‐LEDs and elimination of interfacial reactions caused by the acidic PEDOT:PSS layer for reliable QD‐LEDs. Abstract : P‐type Sb:Cu2 O integrated ITO anode is developed as hole injection layer and anode combined electrodes to substitute acidic PEDOT:PSS HIL based electrode for cost‐effcient and reliable quantum dots light emitting diodes.